ABOUT FIGURATIVE AND INFORMATIVE DOMINANTS OF THE LANDSCAPE ALLEY IN KYIV - Михайлова, Р. Д; Кисіль, С. С. (Art and Design, 2019)
Purpose. An analysis of figurative and informative accents of the Landscape Alley with graphic and design tools in the context of modern improvement of the historical landscape of Kyiv. Methodology. Research was conducted to study the object on the basis of historical and art history, functional, architectural and planning, landscape analysis. For a general assessment of the territory, field surveys, analysis of scientific, journalistic sources and design studies of previous years were carried out. Results. The figurative and meaningful dominants of the Landscape Alley in the historical landscape of Kyiv are determined. The essence and features of art and design tools are revealed during the shaping of its art elements, by combining sculpture with design art. It has been established that the Landscape Alley in Kyiv is an example of a new design thinking of fine art, as an option for designing a recreation zone of a metropolis and is determined by symbiosis: landscape, modern urbanism, traditions of fine art and modern design. Scientific novelty. For the first time, the meaning of the figurative and artistic solution for the arrangement of the Landscape Alley, the product of the collaboration of artists and design, was revealed. As a result, the historical landscape has been turned into a modern gaming, entertaining and comfortable recreational space. The content, role and significance of compositions of park sculptures, art objects of sculptural monumental and decorative plastic in the urban environment are determined. Practical significance. The scientific and practical results of the study can be used in the implementation of landscape-recreational design of urban areas – theme parks, squares, with the development of elements of improvement in them; in computer-aided design of the landscape and the subject environment with it; in the practice of image creation in art and design.